Generating high-yield positrons and relativistic collisionless shocks by 10 PW laser. (6th March 2017) - Jiao, J.; Zhang, B.; Yu, J.; Zhang, Z.; Yan, Y.; He, S.; Deng, Z.; Teng, J.; Hong, W.; Gu, Y.
Abstract: Relativistic collisionless shock charged particle acceleration is considered as a possible origin of high-energy cosmic rays. However, it is hard to explore the nature of relativistic collisionless shock due to its low occurring frequency and remote detecting distance. Recently, there are some works attempt to solve this problem by generating relativistic collisionless shock in laboratory conditions. In laboratory, the scheme of generation of relativistic collisionless shock is that two electron–positron pair plasmas knock each other. However, in laboratory, the appropriate pair plasmas have been not generated. The 10 PW laser pulse maybe generates the pair plasmas that satisfy the formation condition of relativistic collisionless shock due to its ultrahigh intensity and energy. In this paper, we study the positron production by ultraintense laser high Z target interaction using numerical simulations, which consider quantum electrodynamics effect. The simulation results show that the forward positron beam up to 10 13 /kJ can be generated by 10 PW laser pulse interacting with lead target. The estimation of relativistic collisionless shock formation shows that the positron yield satisfies formation condition and the positron divergence needs to be controlled. Our results indicate that the generation of relativistic collisionless shock by 10 PW laser facilities in laboratory is possible.